Application of Multimode Health Education Combined with Humanistic Care in Pain Management of Patients with Femoral Fracture and Its Influence on VAS Score. (13th December 2021) - Shi, Ming; Zhang, Pengyu; Xia, Ling; Wei, Zhiteng; Bi, Fangjie; Xu, Yujia; Wang, Pan
Abstract : Objective . To explore the application of multimode health education combined with humanistic care in pain management of patients with femoral fracture and its influence on VAS score. Methods . A total of 120 patients with femoral fracture admitted in our hospital (May 2017–May 2021) were selected as the research objects. The patients who received routine health education were included into the routine group, and the patients who received multimode health education combined with humanistic care were included into the combined group, with 60 cases in each group. The pain management effect of the two groups was compared after nursing intervention. Results . No significant difference was found in age, BMI, fracture sites, gender, education degree, and residence between the two groups (P  > 0.05). The awareness rate of health knowledge of the combined group was as high as 93.33%, which was obviously higher than that of the routine group (P  < 0.05). Compared with the routine group, excellent rates of sitting durability and joint range of motion in the combined group were obviously higher (P  < 0.05), and poor rates of sitting durability and joint range of motion in the combined group were obviously lower (P  < 0.05). Compared with the routine group, VAS scores of the combined group at 1 d, 2 d, and 3 d after admission and at 1 d, 2 d, and 3 d after surgery were remarkably lower (P  < 0.05). Compared with the routine group, compliance of exercise, medical waist belt using, and working posture of the combined group 1 week, 1 month, and 6 months after surgery was obviously higher (P  < 0.05). Compared with the routine group, the scores of Rasmussen and Johner-Wruhs of the combined group 6 months after surgery were conspicuously higher (P  < 0.05). Conclusion . The application of multimode health education combined with humanistic care in pain management of patients with femoral fracture can effectively relieve pain, improve the awareness rate of health knowledge, promote the recovery of lower limb function, and enhance the prognosis of quality of life for patients.